Effectiveness of simultaneous bilateral visual diaphragm biofeedback under low back pain: influence of age and sex - Molina-Hernández, Nerea; Rodríguez-Sanz, David; Chicharro, José López; Becerro-de-Bengoa-Vallejo, Ricardo; Losa-Iglesias, Marta Elena; Vicente-Campos, Davinia; Marugán-Rubio, Daniel; Gutiérrez-Torre, Samuel Eloy; Calvo-Lobo, César (Frontiers in Physiology, 2024)
Introduction: The aim of the present study was to determine the effectiveness of simultaneous bilateral visual diaphragm biofeedback (BFB) from ultrasonography in conjunction with inspiratory muscle training (IMT) on diaphragmatic thickness during normal breathing and respiratory and clinical outcomes in patients with non-specific low back pain (NSLBP) and determine the influence of age and sex. Methods: A single-blind randomized clinical trial was carried out (NCT04582812). A total sample of 96 patients with NSLBP was recruited and randomized by sex-based stratification into IMT (n = 48) and BFB + IMT (n = 48) interventions over 8 weeks. Bilateral diaphragmatic thickness at maximum inspiration (Tins) and expiration (Texp), respiratory pressures, lung function, pain intensity, bilateral pressure pain threshold (PPT), disability, and quality of life were measured at baseline and after 8 weeks. Results: The BFB + IMT group showed significant differences (p < 0.05) with increased left hemidiaphragm thickness at Tins and Tins-exp (d = 0.38–053), and right and left PPT (d = 0.71–0.74) versus the IMT group. The interaction with sex was statistically significant (p = 0.007; F(1,81) = 7.756; ηp2 = 0.087) and higher left hemidiaphragm thickness at Tins was predicted by the BFB + IMT group (R2 = 0.099; β = 0.050; F(1,82) = 8.997; p = 0.004) and male sex (R2 = 0.079; β = 0.045; F(1,81) = 7.756;p = 0.007). Furthermore, greater left hemidiaphragm thickness at Tins-exp was predicted by younger age (R2 = 0.052; β = −0.001; F(1,82) = 4.540; p = 0.036). Discussion: The simultaneous bilateral visual diaphragm biofeedback by ultrasonography in conjunction with IMT was effective in both increasing the left diaphragmatic thickness during inspiration, which was positively influenced and predicted by male sex and younger age, and increasing the bilateral PPT of the paraspinal muscles in patients with NSLBP.